2003
DOI: 10.1002/itdj.1590100303
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the determinants and effects of ICT diffusion in developing countries

Abstract: Abstract. Using data from developing countries, this paper examines the links between ICT diffusion and per capita income, trade and financial indicators, education, and freedom indicators. Internet hosts, Internet users, personal computers and mobile phones represent indicators of ICT. The Gompertz model of technology diffusion is used to study ICT dissemination. The results show that income and government trade policies influence ICT diffusion. However, freedom indices may or may not affect ICT diffusion. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
156
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(177 citation statements)
references
References 26 publications
8
156
2
1
Order By: Relevance
“…Use of ICT is perceived as catalyzing element in economy and leads to rise effectiveness (Baliamoune-Lutz 2003). The economic interests of ICT-specialized commercial firms (as well as at the international level) are another factor stimulating the development and dissemination of ICT.…”
Section: Factors Affecting the Rebound Effect Of Ictmentioning
confidence: 99%
“…Use of ICT is perceived as catalyzing element in economy and leads to rise effectiveness (Baliamoune-Lutz 2003). The economic interests of ICT-specialized commercial firms (as well as at the international level) are another factor stimulating the development and dissemination of ICT.…”
Section: Factors Affecting the Rebound Effect Of Ictmentioning
confidence: 99%
“…These are just some of the many ways in which ICTs have been shown to bring about improvements in the lives of people. Researchers in the Information Technology for Development field have shown that there is a link between the adoption of ICTs by people in a region and an increase in incomes of people in that region (Baliamoune-Lutz, 2003;Bollou and Ngwenyama, 2008;Cecchini and Scott, 2003;Kottemann and Boyer-Wright, 2009;Kosempel, 2007).…”
Section: Sajda Qureshi Editor-in-chiefmentioning
confidence: 99%
“…The main focus of this paper is on the bridging the digital divide between rural areas per population. Baliamoune-Lutz and Mina, (2003), "An analysis of the determinants and effects of ICT diffusion in developing countries" observes the associations among ICT diffusion and per capita income, trade and financial indicators, education, and freedom indicators. Internet hosts, Internet users, personal computers and mobile phones represent indicators of ICT.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to expectations, ICT diffusion is not associated with education. 1 Poh-Kam Wong, (2002), "ICT production and diffusion in Asia Digital dividends or digital divide?" examines the observed indication to determine whether Asian countries, although having captured a excessively high share of global production of ICT goods, have as a group been straggler in the adoption of ICT in evaluation to non-Asian countries.…”
Section: Introductionmentioning
confidence: 99%